Методические основы анализа инфраструктуры туризма - Вершицкий, А.В. (Культура народов Причерноморья, 2013)
В статье проведен анализ влияния уровня развития туристской инфраструктуры на
вариацию объемов туристского обслуживания в АР Крым. Рассчитаны коэффициенты парной
корреляции для рассматриваемых показателей, на основании метода корреляционных плеяд определены
группы факторов с наиболее сильными внутренними связями. У статті проведено аналіз впливу рівня розвитку туристської інфраструктури на варіацію
обсягів туристського обслуговування в АР Крим. Розраховано коефіцієнти парної кореляції для
розглянутих показників, на підставі методу кореляційних плеяд визначено групи факторів з найбільш
сильними внутрішніми зв'язками. The article analyzes the influence of the development level of tourist infrastructure in the variation of
the volume of tourism services in Crimea. To analyze the tourism infrastructure in Crimea and the tourism
development in the region the system of statistical indicators for 2010-2012 is used. This method allows
determining the direction and the proportion of tourist infrastructure development, taking into account the
expected volume of tourist flows. Correlation with the level of infrastructure development, the number of places
in the specialized accommodation facilities and the total number of tourists in Crimea was not found. That is,
there is certain autonomy, independence of spa facilities, which is determined by many factors, including its
historical development, the existing system of command and control, advanced internal infrastructure of spa
facilities and other factors.
In contrast to the spa facilities, hotels and similar accommodation facilities are much more oriented to the
market of tourist services, the number of tourists served by them has a strong positive correlation with such
indicators as: number of beds in hotels and similar accommodations, shopping area of retail trade, a number of
museums, the number of institutions of cultural and leisure venues (theaters, concert halls), length of roads
paved.
Bivariate correlation coefficients were calculated for the considered parameters on the basis of the correlation
method of defined constellations of the factors with the strongest internal connections. The study identified a
group of indicators of tourism development and infrastructure that have the greatest interference, which allows
identifying priority areas for the development of tourist services.
It is necessary for state and regional authorities, in addition to the tourist products’ advertising and promotion
to pay attention to the proper development of tourist infrastructure in the region.